Metformin and Probiotics Interplay in Amelioration of Ethanol-Induced Oxidative Stress and Inflammatory Response in an In Vitro and In Vivo Model of Hepatic Injury - Farhin Patel; Kirti Parwani; Dhara Patel; Palash Mandal (Mediators of Inflammation)
Alcohol-induced liver injury implicates inflammation and oxidative stress as important mediators. Despite rigorous research, there is still no Food and Drug Administration (FDA) approved therapies for any stage of alcoholic liver disease (ALD). Interestingly, metformin (Met) and several probiotic strains possess the potential of inhibiting alcoholic liver injury. Therefore, we investigated the effectiveness of combination therapy using a mixture of eight strains of lactic acid-producing bacteria, commercialized as Visbiome® (V) and Met in preventing the ethanol-induced hepatic injury using in vitro and in vivo models. Human HepG2 cells and male Wistar rats were exposed to ethanol and simultaneously treated with probiotic V or Met alone as well as in combination. Endoplasmic reticulum (ER) stress markers, inflammatory markers, lipid metabolism, reactive oxygen species (ROS) production, and oxidative stress were evaluated, using qRT-PCR, Oil red O staining, fluorimetry, and HPLC. In vitro, probiotic V and Met in combination prevented ethanol-induced cellular injury, ER stress, oxidative stress, and regulated lipid metabolism as well as inflammatory response in HepG2 cells. Probiotic V and Met also promoted macrophage polarization towards the M2 phenotype in ethanol-exposed RAW 264.7 macrophage cells. In vivo, combined administration of probiotic V and Met ameliorated the histopathological changes, inflammatory response, hepatic markers (liver enzymes), and lipid metabolism induced by ethanol. It also improved the antioxidant markers (HO-1 and Nrf-2), as seen by their protein levels in both HepG2 cells as well as liver tissue using ELISA. Hence, probiotic V may act, in addition to the Met, as an effective preventive treatment against ethanol-induced hepatic injury.